2018
DOI: 10.3390/foods8010010
|View full text |Cite
|
Sign up to set email alerts
|

Olive Leaves Extract from Algerian Oleaster (Olea europaea var. sylvestris) on Microbiological Safety and Shelf-life Stability of Raw Halal Minced Beef during Display

Abstract: Oleaster (wild olive tree) by-products represent a renewable and low-cost source of biopolyphenols. Leaf extracts (sylv.OLE) of Algerian oleaster, locally called a’hachad (Olea europaea subsp. europaea var. sylvestris), were applied at 1 and 5% (v/w) to raw Halal minced beef (HMB) in order to test its safety and shelf-life prolongation during retail/display. The total phenolic compound content in the extract was 198.7 ± 3.6 mg gallic acid equivalent. Ten compounds were identified in the sylv.OLE by High Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 64 publications
(88 reference statements)
3
43
2
Order By: Relevance
“…For investigating the effect of nanoemulsion containing active ingredients, Mohammadi, Jafari, FaridiEsfanjani, and Akhavan () reported that emulsions containing olive leaf extract (oleuropein) covered the undesirable odor of oleuropein and nanoencapsulated oleuropein‐controlled peroxide value better than unencapsulated oleuropein. By adding the olive leaves extract to raw halal minced beef, Djenane, Gómez, Yangüela, Roncalés, and Ariño () reported that the olive leaves extract had not negatively influence the overall acceptability and bitterness of raw halal minced beef that is opposed to present results.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…For investigating the effect of nanoemulsion containing active ingredients, Mohammadi, Jafari, FaridiEsfanjani, and Akhavan () reported that emulsions containing olive leaf extract (oleuropein) covered the undesirable odor of oleuropein and nanoencapsulated oleuropein‐controlled peroxide value better than unencapsulated oleuropein. By adding the olive leaves extract to raw halal minced beef, Djenane, Gómez, Yangüela, Roncalés, and Ariño () reported that the olive leaves extract had not negatively influence the overall acceptability and bitterness of raw halal minced beef that is opposed to present results.…”
Section: Resultscontrasting
confidence: 84%
“…By adding the olive leaves extract to raw halal minced beef, Djenane, Gómez, Yangüela, Roncalés, and Ariño (2018) reported that the olive leaves extract had not negatively influence the overall acceptability and bitterness of raw halal minced beef that is opposed to present results.…”
Section: Sensory Analysiscontrasting
confidence: 99%
“…EOs were weighted and conserved at 4°C until use. Total phenolic compounds in the L. nobilis EO were estimated spectrophotometrically according to the Folin–Ciocalteu method with some modifications (Djenane et al., 2019). Gallic acid (GA) was used as phenolic compound standard for the calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…In view of their different biological properties, EOs have shown important antimicrobial activities that can be used for the control of the contamination by molds and mycotoxins in agricultural commodities (Abd El‐Aziz, Mahmoud, Al‐Othman, & Al‐Gahtani, 2015; Ben Miri et al., 2018; Bluma, Amaiden, Daghero, & Etcheverry, 2008; Tian et al., 2012). EOs can also be used as flavoring or food additives (Taoudiat, Djenane, Ferhat, & Spigno, 2018), as well as antioxidants and antibacterial agents in foods (Djenane, Gómez, Yangüela, Roncalés, & Ariño, 2019), whose utilization has been authorized in the USA (FDA, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation